The African Development Foundation (ADF) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The African Development Foundation (ADF)The African Development Foundation (ADF) was founded in l980 by the US Congress and has been working actively since 1984. Its aim is to give economic aid to African institutions, groups or individuals taking...